Investigating the Rossler Attractor Using Lorentz Plot and Lyapunov Exponents - Kvarda, P. (Radioengineering Society, 2002)
To investigate the Rossler attractor, introduced in 1976 by O.E. Rossler [3], we used Lorenz plot to show deterministic character and designated the Lyapunov exponent to show the chaotic character of the system.
Keywords: Deterministic chaos; Rössler attractor; Lorenz plot; Lyapunov exponent